Water and soil conservation of vetiver hedges planted in young rubber plantation on slope land - Wang Yuekun; Lin Weifu; Xie Guishui (IRRDB Conference: NR Industry: Responding to Globalization 7-8 September 2004, Kunming International Convention & Exhibition Center, China)
An experiment was conducted to study the water and soil conservation of Vetiver (Vetiveria zizaanioides) hedges established in a one-year-old rubber plantation. One to two rows of vetiver were planted with space of 20 cm between vetiver bushes at the outer slope of contour ledge on 23o-slope land. The vetiver hedges were basically established after 18 months. During 18-30 months after planting vetiver, the critical rainfall causing runoff under treatment II, two vetiver hedges, was 1.2 mm higher than that under the control, the conventional contour ledge; and runoff and soil erosion under treatment II were respectively 27.2;and 26.7;less than that under the control. During 6-30 months after planting vetiver, erosive soil was accumulated by 2.4 cm in depth at the upside of vetiver hedges under treatment II, while the soil was eroded by 1.8 mm in depth at the outer slope under the control, and no disadvantageous effect of vetiver hedges on the growth of rubber trees was found. These results showed that vetiver hedges are beneficial in the respect of water and soil conservation once they were basically established. But the value of vetiver hedges and ecological adaptability of vetiver in rubber plantation would need further research.
Keywords: Rubber plantation; Vetiver; Water and soil conservation